Dragon Fruit, Guava, and Honey Juice (Take Care of Your Mother) - Jenny Anna Siauta; Suci Septania Puspa; Erviana Magdalena L; Sari Wulandari; Mira Saraswati; Marta Dessy Sianturi; Syaffitry Maryany; Elvi Mardiyanti; Mahayanti Arum W (International Journal of Community Services, 2024)
World Health Organization (WHO), 40% of pregnant women worldwide suffer from anemia. Anemia in pregnancy is a condition where pregnant women have Hb levels <11.00 gr% in the first, second, and third trimesters or Hb levels <10.50 gr% in the second trimester, because there is a difference in hemodilution, especially in the second trimester. Anemia that occurs during pregnancy can be caused because many women start their pregnancy with insufficient food reserves or experience anemia before pregnancy. The most common anemia in pregnancy is iron deficiency anemia, which is caused by a lack of nutrition from food. Natural ingredients that can be used as an alternative to treat anemia and are easy to obtain and cultivate also contain protein, vitamin C, and iron. One non-pharmacological method or natural ingredient that can be used to increase Hb levels is dragon fruit juice, red guava, and honey. The study's conclusion (Meilinda V et al., 2023) is that dragon fruit juice (Hylocereus Polyrhizus) and honey affect increasing Hb levels in pregnant women with anemia. This community service was carried out to overcome priority problems found in the Tanah Tinggi Sub-Health Center, Central Jakarta, namely Anemia in Pregnant Women. The method used in this community service is using lectures, discussions, and demonstrations. Targeting pregnant women with anemia The results of this community service, help pregnant women understand and understand the counseling and complementary therapy "Take Care of Your Mother" which can be applied to overcome Anemia.